Role of Myocardial Infarction-Induced Neuroinflammation for Depression-Like Behavior and Heart Failure in Ovariectomized Female Rats. (1st September 2019) - Najjar, Fatimah; Ahmad, Monir; Lagace, Diane; Leenen, Frans H.H.
Abstract: After myocardial infarction (MI), ovariectomized (OVX) female rats develop depression-like behaviors and an increase of pro-inflammatory cytokine (PIC) levels in the prefrontal cortex (PFC). We hypothesized that inhibition of neuroinflammation by the PIC synthesis inhibitor, pentoxifylline (PTX) would prevent depression-like behaviors induced by heart failure (HF) post-MI in OVX female rats. PTX treatment was initiated in female Wistar rats, 1 week after ovariectomy, and 1 week before MI by occlusion of the left anterior descending artery. Eight weeks post-MI, OVX female rats treated with vehicle or PTX exhibited a similar MI size and degree of cardiac dysfunction. OVX female rats post-MI developed depression-like behaviors consisting of anhedonia, despair behavior and enhanced freezing behavior in the cued conditioning test. PTX prevented the depression-like behavior symptoms and enhanced freezing. Cytokine levels were elevated in plasma and both paraventricular nucleus (PVN) and PFC, and the mature brain-derived neurotrophic factor (mBDNF) was decreased in the PFC of OVX female rats post-MI. PTX treatment limited the decrease of mBDNF, and decreased cytokine levels in plasma, PVN and PFC to (below) sham levels. These findings show that OVX female rats post-MI exhibit an increase in both peripheral and central inflammation. PTX treatment prevents increases in PIC levels in plasma and PVN but does not attenuate the progression of cardiac dysfunction. In contrast, PTX prevents enhanced PIC production in the PFC, as well as limits depression-like behaviors induced by MI in OVX female rats. Graphical abstract: The increase in plasma cytokines, Ang II and aldosterone post MI can induce neuroinflammation in CVOs such as the SFO that in turn increases local production of cytokines, reactive oxygen species, and AngII-AT1R signaling in the PVN leading through the RVLM to increase of sympathetic nerve activity. PVN, NTS and RVLM projections increase LC activity which increases norepinephrine release in the PFC, stimulating microglia activity inducing local cytokine production and decreasing mBDNF levels. PFC activation may disinhibit amygdala and increase mBDNF levels and freezing behavior. Peripheral cytokines also stimulate the afferent vagus nerve that projects to dorsal complex and NTS through activating catecholamine neurons in the NTS and RVLM leads to increase CRF release in the PVN and activation of HPA axis.Unlabelled Image Highlights: OVX female rats post-MI develop depression-like behavior with increase in cytokines in CNS (91). PTX prevents neuroinflammation and prevents the behavioral changes after MI (76). PTX had no impact on the progression of cardiac dysfunction in OVX female rats post MI (85).